2007
DOI: 10.1103/physreve.76.031116
|View full text |Cite
|
Sign up to set email alerts
|

Heat conduction in quantum harmonic chains with alternate masses and self-consistent thermal reservoirs

Abstract: We consider the analytical investigation of the heat current in the steady state of the quantum harmonic chain of oscillators with alternate masses and self-consistent reservoirs. We analyze the thermal conductivity kappa and obtain interesting properties: in the high temperature regime, where quantum and classical descriptions coincide, kappa does not change with temperature, but it is quite sensitive to the difference between the alternate masses; and contrasting with this behavior, in the low temperature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…heat transfer is diffusive [22][23][24][25]. SCTB model has also been applied to investigating quantum effects in non-ballistic heat transfer [24][25][26][27], effects of additional anharmonicity [23,[28][29][30] and unequal masses [31][32][33] on heat conduction and the necessary ingredients of thermal rectification [27,[34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…heat transfer is diffusive [22][23][24][25]. SCTB model has also been applied to investigating quantum effects in non-ballistic heat transfer [24][25][26][27], effects of additional anharmonicity [23,[28][29][30] and unequal masses [31][32][33] on heat conduction and the necessary ingredients of thermal rectification [27,[34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the model was revisited by Roy and Dhar [20,21], who demonstrated that under the linear response assumption and for asymptotically long chains, Fourier's law holds and a temperature dependent thermal conductivity is realized. An analytical study of the SC model with alternate masses has revealed the role of quantum effects at low temperatures [22,23]. More recently, a mathematical analysis of the mass-graded SC model in the quantum domain has indicated on the onset of thermal rectification, beyond the linear response regime [24].…”
Section: Introductionmentioning
confidence: 99%
“…Anyway, even if we discard any relation with anharmonicity, these results show, at least, that the onset of Fourier's law does not guarantee thermal rectification in asymmetric classic models -we recall that the Fourier's law does not hold in standard harmonic systems (i.e., harmonic models with reservoirs at the boundaries only), but it holds in the SC models.Still searching for the mechanism behind the rectification in graded mass systems, we recall that, at low temperatures, quantum effects may introduce significant changes. The thermal conductivity for the quantum self-consistent harmonic chain (QSC), for example, depends on temperature [8,26], in opposition to the CSC thermal conductivity [7]. Thus, searching for possible quantum effects in the mechanism of thermal rectification, in a quite recent work [27], we turn to the inhomogeneous QCS and, in the linear response regime, i.e., for the chain submitted to a very small gradient of temperature and considering only linear corrections in computations with changes in the temperature, we show the absence of thermal rectification despite quantum effects in the conductivity.…”
mentioning
confidence: 99%
“…( 4) and necessary to study F l , may be a very difficult task -we know a precise solution for some specific cases: e.g., for a homogeneous next-neighbors interparticle interaction and all particles with the same mass M W = mI [8]; and also for the case of particles with alternate masses, i.e. m j = m 1 for j odd, and m j = m 2 for j even [26]. Hence, we first restrict our interparticle interaction Φ to the homogeneous nearestneighbor case, i.e., Φ = −∆, the lattice Laplacian, and study the equations for the smallest possible chain: N = 3 (it is, in fact, a cell of a large chain).…”
mentioning
confidence: 99%